Key Plant, Key Pests: Holly (Ilex sp.) - Juanita Popenoe; Caroline Roper Warwick; Jacqueline Bourdon; Liz A. Felter (EDIS, 2019)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists, and landscape professionals to help identify common pests associated with common Florida flora. This publication, the eighth in the Key Plant, Key Pests series, helps identify the most common pests found on Holly (Ilex sp.). This publication provides information and general management recommendations for Florida wax scale, tea scale, Cylindrocladium leaf spot, dieback, Sphaeropsis gall, root knot nematodes, and magnesium deficiency. This five-page document was written by Juanita Popenoe, Caroline R. Warwick, Jacqueline Bourdon, and Liz Felter and published by the UF/IFAS Department of Environmental Horticulture. http://edis.ifas.ufl.edu/ep566